# Y = (6x4 – 5x3 + 2x + 3)6, find dydx Solution: Given, y = (6x4 – 5x3 + 2x + 3)6 Let u = [6x4-5x3+□+3] ∴ y = u□ ∴ dydu = 6u6–1 ∴ dydu = 6( )5 and dudx=24x3-15(□)+2 By chain rule, dydx=dy□×□dx ∴ - Mathematics and Statistics

Fill in the Blanks
Sum

y = (6x4 – 5x3 + 2x + 3)6, find ("d"y)/("d"x)

Solution: Given,

y = (6x4 – 5x3 + 2x + 3)6

Let u = [6x^4 - 5x^3 + square + 3]

∴ y = "u"^square

∴ ("d"y)/"du" = 6u6–1

∴ ("d"y)/"du" = 6(  )5

and "du"/("d"x) = 24x^3 - 15(square) + 2

By chain rule,

("d"y)/("d"x) = ("d"y)/square xx square/("d"x)

∴ ("d"y)/("d"x) = 6(6x^4 - 5x^3 + 2x + 3)^square xx (24x^3 - 15x^2 + square)

#### Solution

Given,

y = (6x4 – 5x3 + 2x + 3)6

Let u = [6x4 – 5x3 + 2x + 3]

∴ y = "u"^6

∴ ("d"y)/"du" = 6u6–1

∴ ("d"y)/"du" = 6(u)5

and "du"/("d"x) = 24x^3 - 15x^2 + 2

By chain rule,

("d"y)/("d"x) = ("d"y)/"du" xx "du"/("d"x)

∴ ("d"y)/("d"x) = 6(6x^4 - 5x^3 + 2x + 3)^5 xx (24x^3 - 15x^2 + 2)

Concept: Derivatives of Composite Functions - Chain Rule
Is there an error in this question or solution?